Finding the fair(way): utilizing community engagement strategies to re-envision a vacant golf course in Overland Park, Kansas - Jundt, Hayden (Kansas State University, 2024)
Golf course closures have become an increasing problem in the United States for over a decade. This problem falls on the residents of surrounding communities to defend their neighborhood from an influx of redevelopment plans, all while typically having limited input into what happens after a golf course closes. These issues lead to an abundance of conflict concerning vacant golf courses due to the contrasting opinions of stakeholder groups. Thus, this study aims to answer the research question, “How can vacant golf courses be re-envisioned to balance the interests of developers and residents of surrounding communities?” To answer the research question, this project identifies common issues and dilemmas among various stakeholders concerning the redevelopment of Deer Creek Golf Club, explores relevant community engagement and design approaches through a case study analysis process, and proposes a scenario-based design for re-envisioning a vacant golf course, Deer Creek Golf Club. This study investigates how past examples of community engagement were utilized in the design process to address conflict and explore resolutions for repurposing vacant golf courses. This project utilizes document reviews, city council meeting agendas and minutes, and adequate site and community analyses to understand land use dilemmas and redevelopment issues. Case studies involving public perception summaries and stakeholder interviews with professionals were conducted to obtain insight into the community engagement processes involved in recent golf course development projects. Specifically, this study applies what the investigator learns from the document review and case study analysis processes to develop a hypothetical design for Deer Creek Golf Club. The research outcomes of this study provide greater insight into the differing opinions regarding redevelopment plans for vacant golf courses and how community engagement in design can help address and solve the problem. The results highlight the usability of community engagement strategies to resolve conflict among residents surrounding vacant golf courses in the U.S.
Keywords: Vacant golf course redevelopment